The diagnostic value of RDW in appendicitis - Mahboub Pouraghaei; Payman Moharamzadeh; Hadi Khoshakhlagh; Yaghoub Asheghvatan (Journal of Research in Clinical Medicine, 2023)
Introduction: Diagnosis of acute appendicitis is based on clinical manifestation .Some patients have atypical clinical symptoms, and diagnosis is difficult. Red blood cell distribution width (RDW) is a measure of heterogeneity in the size of circulating red blood cells. The aim of this study was to evaluate RDW values in diagnosis of appendicitis. Methods: This is a retrospective case-control study, in which 399 patients with pathological diagnosis of appendicitis were divided into two groups of acute appendicitis and complicated appendicitis and compared with 400 healthy controls for appendicitis. RDW, white blood cell (WBC), platelet count (PLT), and hemoglobin changes were compared in three groups of patients. Results: In all three groups, the ratio of men was significantly higher than women (P<0.05). WBC (P=0.00), PLT (P=0.01), and RDW (P=0.01) had a significant difference between the three groups. However, there was no significant difference in the hemoglobin level between the three groups (P=0.3). RDW level was significantly higher in complicated appendicitis compared to acute (P=0.09) and control group (P=0.012). Conclusion: The results of this study showed that RDW value in three groups were significantly different. However, these values are not clinically useful for detecting appendicitis due to the slow progression of RDW value in patients.